Understanding the reasons that hinder mobile e-book use of university mathematics students - Letchumanan, Malathi; Mohamad, Mariam; Davrajoo, Elenchothy (Institute for Mathematical Research, Universiti Putra Malaysia, 2019)
This study determined the issues related to usage of mathematics mobile e-book and how these issues affected the learning process of the participants. The study used qualitative case study design. Eight postgraduate Mathematics students from Abstract Algebra research group from a local public university in Malaysia were interviewed and observed. The data were analysed in terms of content analysis and descriptive analysis. The findings showed that, utilitarian, affective and cognitive reasons affected the learning activities of the participants negatively. It is concluded that, this study contributed in terms of expanding readers understanding on the reasons that demotivates the usage of mobile e-books and how it's dampen the learning process of the participants.